On the Commutative Rings with At Most Two Proper Subrings - David E. Dobbs (International Journal of Mathematics and Mathematical Sciences, 2016)
The commutative rings with exactly two proper (unital) subrings are characterized. An initial step involves the description of the commutative rings having only one proper subring.